The effects of acitretin on ovarian reserve: An experimental study in rats - Münevver Güven; Tolga Atakul; Serkan Yaşar Çelik; Mustafa Yılmaz; Buket Demirci (Galenos Publishing House, 2022)
Background and Design: Acitretin is widely used on many dermatological diseases. No adequate studies have evaluated its effects on ovarian reserve. Thus, this experimental study aimed to investigate the possible effects of acitretin on ovarian reserve by examining ovarian follicle counts and serum anti-Mullerian hormone (AMH) values. Materials and Methods: This study randomly distributed 31 female Wistar albino rats into 3 groups including one control group (group 1) and two equal experimental groups. Acitretin was given at doses of 0 mg/kg/day (group 1, n=11), 1 mg/kg/day (group 2, n=10), and 5 mg/ kg/day (group 3, n=10) for 4 weeks. All the rats in three groups were kept drug-free for 4 weeks before being sacrificed. The blood samples and both ovarian tissues were obtained from the rats. Serum values of AMH were assessed and the number of ovarian follicles was counted by histopathological examination. Results: The AMH levels were lower in both acitretin groups (groups 2 and 3) than group 1. However, no significant difference was found between the groups in terms of AMH values (p=0.338). Primordial, secondary, tertiary, and total follicle numbers in group 3 were statistically lower than that of groups 1 and 2. The number of primary follicles in group 1 was statistically higher than that of groups 2 and 3. Additionally, the number of secondary follicles in group 2 was statistically higher than that of group 1. Conclusion: This study showed that ovarian reserve can be affected by acitretin treatment. Particularly, high doses of acitretin may reduce ovarian reserve. Further experimental and clinical studies are needed to clarify the effect of acitretin on ovarian reserve.